Dynamics of the Intellectual Tradition of Ulama Dayah Aceh - Syadidul Kahar (Lakhomi Journal Scientific Journal of Culture, 2021)
This research provides information about the intellectual dynamics of dayah ulama Aceh. The goal is to find a common thread between tradition and modernization in dayah ulama Aceh scholarship. This research is a historical research using a social history approach. Based on the results of data analysis, the research results show that the role of the dayah is a realization of the intellectual manifestation of the dayah ulama Aceh. Dayah is used as a forum to teach various knowledge of Islamic teachings with a curriculum based on classical books or turats by maintaining the faith of experts in the sunnah wal jamaah. Based on the historical dynamic journey, dayah still exists as a fortress and a place for cadre generations to understand the teachings of Islam. So, Acehnese dayah intellectuals emphasize more on understanding classical books with actual contexts. So, the demands of the changing times provide its own dynamics to the intellectuals of the dayah ulama Aceh, but in this case the emphasis is that Islamic teachings through dayah continue to exist.